POLICY IMPLEMENTATION OF AGRICULTURAL WAREHOUSE RECEIPT SYSTEM OF AGRICULTURAL PRODUCTS IN EAST JAVA - Sulistyaningsih Sulistyaningsih; Rudi Wibowo; Evita Soliha Hani; Yuli Hariyati (UNEJ e-Proceeding)
This research examines various variables in the implementation of Warehouse Receipt System in East Java in 6 SRG sample districts. The method used is Decision Matrix Analysis (DMA) with 5 price variables, infrastructure, cost, government support, and warehouse receipt utilization. SRG in general in the area of study has not been well utilized, therefore it is necessary: (1) comprehensive efforts, integrated and accelerated by all stakeholders, especially from relevant agencies. (2) government support in terms of socializing the benefits and uses of SRG in the marketing of farmer's results and income. (3) the existence of new institution such as small warehouse of container unit in central area or at remote location so that it can accommodate small farmers and distance of distant business location. (4) Provision of transportation to assist in transportation of goods. (5) management of SRG, since SRG has been built with central allocation fund, while those who provide land is the region, the uncertainty of making local governments halfhearted in managing SRG. (6) maintenance of sustainable infrastructure for future development.